Proceeding of 2021 International Conference on Wireless Communications, Networking and Applications - Qian, Zhihong; Jabbar, M.A; Li, Xiaolong (Lecture Notes in Electrical Engineering,, 2022)
This open access proceedings includes original, unpublished, peer-reviewed research papers from the International Conference on Wireless Communications, Networking and Applications (WCNA2021), held in Berlin, Germany on December 17-19th, 2021. The topics covered include but are not limited to wireless communications, networking and applications. The papers showcased here share the latest findings on methodologies, algorithms and applications in communication and network, making the book a valuable asset for professors, researchers, engineers, and university students alike. This is an open access book.